A planet in distress with discarded face masks, disposable plastics. - Bahrudin, Fadzli Irwan; Suib, Sarah; Mahat, Mohd Muzamir (New Straits Times Press, 2021)
The article highlights that current plastics consumption is worrisome. Though plastic products are essential to mitigate the contagion of Covid-19, a reform plan is needed to alleviate the plastic crisis. The authors suggest a change of consumer behaviour, implementation of an efficient waste management system and a rigour exploration of environmentally benign materials to solve the plastic problem, amid our battle with the coronavirus.